Consistency of Magnetic Susceptibility Values in Raw Mix 2 using Bartington Magnetic Susceptibility Meter Sensor Type B - Kolotosa, Julio Fadjar; Hamdi, Hamdi; Mufit, Fatni; Dwiridal, Letmi (Journal of Experimental and Applied Physics, 2024)
The process of making cement goes through quite long stages, one of the processes is grinding at the Raw Mill. Raw Mill is divided into two large groups, Horizontal Mill and Vertical Mill, in Horizontal Factory. The milling result at the Horizontal Mill is Raw Mix 2 and quality testing will be carried out. In quality testing, testing is usually carried out on chemical parameters and there is no testing based on physical parameters. By looking for the magnetic susceptibility score of raw cement samples in Raw Mix 2 using the Bartington Magnetic Susceptibility Meter Type B sensor, you can see the consistency of magnetic minerals in raw cement in Raw Mix 2. Samples were taken from the Padang Semen Factory every hour of every day from February 1 to February 10, 2022, the samples were then measured using the Bartington Magnetic Susceptibility Meter Type B Sensor. The measurement results showed that the magnetic susceptibility value of Raw Mix 2 ranged from 79.8 x/kg to 206.9 x/kg, and standard deviation calculations were used. The data is interpreted into a graph and it shown that the magnetic susceptibility value of Raw Mix 2 obtained can be said to be consistent and of good quality. The magnetic properties of Raw Mix 2 obtained according on the magnetic susceptibility score obtained are antiferromagnetic. The grain type in Raw Mix 2 was found to have almost no superparamagnetic grains or contained less than 10% superparamagnetic grains.